PERAN KKN R7 SEBAGAI FASILITATOR DALAM PEMBERDAYAAN KELOMPOK WANITA TANI DUSUN KROMODANGSAN MELALUI PENANAMAN BIBIT SAYURAN ORGANIK (ECO-FRIENDLY) DENGAN MEMANFAATKAN LAHAN PEKARANGAN - Susanti, Fathonah Eka; Titi Laras; Nining Widiyanti; Bambang Jatmiko; Septi Silovani Andini; Budi Anggoro Sajiwo Putro; Wahyu Romadan; Heti Oktavya Kunthi Eka Risti; Joya Delarosa; Muhamad Iklas Sul Amal; et al. (JURNAL PENGABDIAN MANDIRI, 2025)
This article discusses the role of the R7 Community Service Program (KKN) of Janabadra University as a facilitator in empowering the Kromodangsan Hamlet Farmer Women Group through planting organic (eco-friendly) vegetable seeds in the yard of the houseThis activity aims to increase public awareness of the importance of environmentally friendly agriculture and strengthen the role of women in sustainable natural resource management. The planting of organic vegetable seeds includes crops such as mustard greens, tomatoes, chili, celery, leeks, and others, which are expected to provide economic benefits through increasing agricultural yields, as well as supporting environmental conservation by reducing the use of chemicals in farming. The results of this activity show that there is an increase in the knowledge and skills of members of the Women Farmers Group in organic vegetable cultivation, as well as strengthening family food security. Collaboration between KKN students and local communities has proven to be effective in creating a positive impact on women's empowerment and environmental sustainability in Kromodangsan Hamlet